2014
DOI: 10.1177/1535370214564755
|View full text |Cite
|
Sign up to set email alerts
|

Daidzein enhances intramuscular fat deposition and improves meat quality in finishing steers

Abstract: An experiment was conducted to determine the effects of soy isoflavone daidzein on carcass characteristics, fat deposition, meat quality, and blood metabolites in finishing steers. Fourteen crossbred steers were used in a 120-d finishing study. These steers were stratified by weight into groups and randomly allotted by group to one of two dietary treatments: (1) control and (2) daidzein (500 mg/kg concentrate). The steers were fed a 90% concentrate diet. Supplemental daidzein did not affect slaughter weight, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…There was a greater concentration of daidzein in SH than in SHS, indicating that the saponins might increase the microbial utilization of daidzein, which would be beneficial to animals. Previous results suggested that supplemental daidzein can affect lipid metabolism by enhancing intramuscular fat deposition and improves meat quality in finishing steers (Zhao et al, 2015). Squalene is an intermediate metabolite in the synthesis of cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…There was a greater concentration of daidzein in SH than in SHS, indicating that the saponins might increase the microbial utilization of daidzein, which would be beneficial to animals. Previous results suggested that supplemental daidzein can affect lipid metabolism by enhancing intramuscular fat deposition and improves meat quality in finishing steers (Zhao et al, 2015). Squalene is an intermediate metabolite in the synthesis of cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…Thesoy isoflavone, daidzein, is used as a phytoestrogen for treating cardiovascular disease [10], osteoporosis [11] and lower cholesterol [12]. Moreover, daidzein has been reported to inhibit the proliferation of human breast cancer MDA-MB-453 cells [13]and cervical cancer Hela cells in vitro [14].…”
mentioning
confidence: 99%
“…Some researchers have shown that daidzein has a positive effect on fat deposition. Zhao et al (2015) found that daidzein supplementation significantly increased the IMF content of crossbred steers. Li et al (2011) and Rehfeldt et al (2007) reported that adding a high dose of daidzein significantly increased the fat proportion in carcases of Guangxi minipig and piglets, respectively.…”
mentioning
confidence: 92%
“…Daidzein has been reported to be effective at affecting the meat quality of animals, but a few animal studies published have given conflicting results. Zhao et al (2015) found that daidzein supplementation improved the tenderness of beef by increasing the intramuscular fat (IMF) content and marbling score. On the other hand, Rehfeldt et al (2007) reported that supplemental daidzein changed the muscle fibre type in piglets.…”
Section: Introductionmentioning
confidence: 99%